2002
DOI: 10.1002/stc.10
|View full text |Cite
|
Sign up to set email alerts
|

Some issues related to the feedback control of a baffled plate

Abstract: This paper addresses a few issues related to the active structural acoustic control (ASAC) of a baffled plate. The first part proposes a feedback control strategy according to which a SISO control system is built by using a volume displacement sensor and a set of actuators driven with a single amplifier. The location of the actuators is then optimized to achieve an open‐loop transfer function with alternating poles and zeros, as for systems with co‐located actuators and sensors. This important feature allows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Figure 5 shows the results for the radiation efficiency of the first six axisymmetric modes for a clamped plate predicted using Eqs. (11), (14), (36), and (37). Figure 6 presents the same results for a simply-supported plate.…”
Section: Radiation From the Structural Axisymmetric Modesmentioning
confidence: 73%
See 2 more Smart Citations
“…Figure 5 shows the results for the radiation efficiency of the first six axisymmetric modes for a clamped plate predicted using Eqs. (11), (14), (36), and (37). Figure 6 presents the same results for a simply-supported plate.…”
Section: Radiation From the Structural Axisymmetric Modesmentioning
confidence: 73%
“…Therefore, comparing with Eq. (14), Eq. (20) is identified as a quantity proportional to the sound radiation efficiency of the sound source.…”
Section: Eigenanalysis Of the Resistance Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of the effective piezoelectric properties to achieve a volume velocity sensor has been computed according to the theory described in. 2,6,7 Like in the previous example, the electrode density has been taken proportional to the effective piezoelectric properties, without correction to account for tridimensional effects in the electric field distribution within the thickness of the piezo film. The test plate is mounted in an aluminium frame and the simply supported boundary conditions are materialized by a dual elastomer joint (on both sides) with a circular cross section.…”
Section: Test 2: Volume Velocity Sensor Of a Simply Supported Platementioning
confidence: 99%
“…Although the spatial filtering of plates and shells with two-dimensional PVDF films has been suggested, 5 it has never been implemented in practice, for lack of capability of continuously shaping the piezoelectric properties of the sensor material. A way to turn around this difficulty by a proper electrode design was proposed by the present authors, [6][7][8] and applied to a cantilever beam covered with a two-dimensional PVDF film (copolymer) 2 ; this test compared the classical modal filter of the beam theory with the corresponding profile obtained with the new porous electrode; it showed that (i) the two electrodes give the same result, but (ii) none of them constitutes a good modal filter when the piezoelectric film is isotropic (d 31 = d 32 ). This somewhat puzzling result has been confirmed with finite element calculations using shell elements.…”
Section: Introductionmentioning
confidence: 96%